2014
DOI: 10.1002/art.38573
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Adaptive Cytokine and Shed Tumor Necrosis Factor Receptor Levels Are Elevated Preceding Systemic Lupus Erythematosus Disease Flare

Abstract: Objective Systemic lupus erythematosus (SLE) is a multifaceted disease characterized by immune dysregulation and unpredictable disease activity. This study evaluated changes in plasma concentrations of soluble mediators preceding clinically-defined disease flares. Methods Soluble mediators (n=52) were examined, including cytokines, chemokines, and soluble receptors, using validated multiplex bead-based or enzyme-linked immunosorbent assays in plasma from European American SLE patients who developed disease f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 45 publications
(90 reference statements)
11
109
2
2
Order By: Relevance
“…These findings support the idea that alterations in the balance between inflammatory and regulatory mediators may help identify patients at risk of disease flare and help decipher SLE pathogenic mechanisms [84]. Concerning the role of regulatory T cells in SLE, most studies point to a reduction in Treg cell number and function in SLE [85][86][87].…”
Section: Cytokines and Immune-regulatory Defectssupporting
confidence: 71%
See 1 more Smart Citation
“…These findings support the idea that alterations in the balance between inflammatory and regulatory mediators may help identify patients at risk of disease flare and help decipher SLE pathogenic mechanisms [84]. Concerning the role of regulatory T cells in SLE, most studies point to a reduction in Treg cell number and function in SLE [85][86][87].…”
Section: Cytokines and Immune-regulatory Defectssupporting
confidence: 71%
“…Recently, an interesting study evaluated changes in plasma concentrations of soluble mediators preceding clinically-defined disease flares in SLE. They found that patients with impending flare had significant alterations in a wide variety of soluble mediators at baseline with significantly higher levels of pro-inflammatory mediators, including Th1, Th2, and Th17-type cytokines, several weeks before clinical flare compared to clinically stable patients [84]. Levels of regulatory cytokines, including IL-10…”
Section: Cytokines and Immune-regulatory Defectsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) of SLE patients show increased Adam17 expression (9). Soluble shedding substrates of ADAM17 have been found in the plasma and urine of lupus mice and SLE patients, and some of these soluble factors are elevated prior to flare (10)(11)(12). Among these, 2 major ADAM17 substrates, TNF-α and heparin-binding EGF (HB-EGF) (7,8), have been separately implicated as important mediators of kidney damage in lupus (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty cytokines, chemokines, and other soluble mediators were assessed by xMAP multiplex assays (Panomics/Affymetrix, Santa Clara, CA), as previously described (22). Multiplex soluble-mediator data were analyzed on the BioPlex 200 array system (Bio-Rad Technologies, Hercules, CA) with a lower boundary of 100 beads per analyte per sample.…”
Section: Methodsmentioning
confidence: 99%